2012
DOI: 10.3389/fnins.2012.00013
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning Oligodendrocyte Development by microRNAs

Abstract: Myelination of axons by oligodendrocytes in the central nervous system is essential for normal neuronal functions. The failure of remyelination due to injury or pathological insults results in devastating demyelinating diseases. Oligodendrocytes originate in restricted regions of the embryonic ventral neural tube. After migration to populate all areas of the brain and spinal cord, oligodendrocyte precursors undergo a temporally well-defined series of molecular and structural changes, ultimately culminating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 74 publications
1
43
0
4
Order By: Relevance
“…Multiple miRNAs have been associated with oligodendrocyte maturation during embryonic development [15,18,20,21]. Whether these miRNAs play important roles in adult oligodendrocytes are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple miRNAs have been associated with oligodendrocyte maturation during embryonic development [15,18,20,21]. Whether these miRNAs play important roles in adult oligodendrocytes are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Using miRNA array, several studies have identified miRNAs related to oligodendrocyte maturation [1517]. Multiple miRNAs including miR-219, miR-138, miR17-92 and miR-338 have been found to modulate the proliferation or differentiation of OPCs into mature oligodendrocytes [15,1822]. However, the functional roles of miRNAs in stroke-induced oligodendrogenesis have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…At each stage, cells can be identified and isolated on the basis of temporally regulated surface antigens, which permit the selection of cells of defined mitotic and differentiation potential (Ishibashi et al, 2004;Nishiyama et al, 2009;Yuan et al, 2011;Zhang, 2001;Zhao et al, 2012). These discrete stages exhibit distinct miRNA profiles as well, that may serve to regulate translation, and thus sharpen phenotypic transitions during lineage progression (Barca-Mayo and Lu, 2012;Dugas et al, 2010;He et al, 2012;Lau et al, 2008;Mallanna and Rizzino, 2010;Shenoy and Blelloch, 2014;Shi et al, 2010;Zhao et al, 2010). AEP, anterior entopeduncular nucleus; ICM, inner cell mass; LGE, lateral ganglionic eminence; LV, lateral ventricle; MGE, medial ganglionic eminence.…”
Section: Oligoneogenesis In the Forebrainmentioning
confidence: 99%
“…Since the role of microRNAs in myelinating glia has been a very active area of investigation, several excellent reviews have recently covered various aspects of microRNA regulation (Barca-Mayo and Lu, 2012; Dugas and Notterpek, 2011; He et al, 2011; Zheng et al, 2012). Initial studies of microRNA function in myelinating glia have focused on microarray profiling and using knockouts of Dicer, which is required for formation of mature microRNAs.…”
mentioning
confidence: 99%